Main tendencies of the Internet development in the future and new Internet professions - Khymytsia, Natalia; Kolos, Sofia (Видавництво Львівської політехніки, 2017)
The prospects of the emergence of new ITprofessions are considered, according to the latest forecasts of the future development of the Internet
Keywords: the Internet; information activities; the future; IT- professions